The establishment of reintroduced Eurasian lynx (Lynx lynx) in a forest-dominated low mountain range: habitat use and predation patterns - Tröger, Carolin (2022)
Understanding the influence of a predator on its prey and the resulting changes in prey behaviour and/or abundance is a widely-discussed subject in wildlife ecology, yet large gaps in knowledge remain. In addition, the return of a long absent predator in our human-altered environment prompts conflicts of human interests, especially among hunters and livestock breeders. Hence, understanding the predator-prey dynamics is a highly interesting topic scientifically as well as from an applied management perspective regarding the forest-game conflict. At the same time, studying habitat selection of large carnivores in our human-dominated landscape provides valuable information about their habitat requirements and adaptation to human disturbance. This supports management implications to establish and maintain viable metapopulations connected through corridors and thus can ensure genetic exchange. This thesis contributes in addressing this topic, aiming to investigate the establishment of newly reintroduced lynx (Lynx lynx) and its effect on the main prey species in a forest-dominated low mountain range in Germany.